Makers : a history of American studio craft - Koplos, Janet (University of North Carolina Press, 2010)
Here is the first comprehensive survey of modern craft in the United States. The book follows the development of studio craft--objects in fiber, clay, glass, wood, and metal--from its roots in 19th-century reform movements to the rich diversity of expression at the end of the 20th century. Keeping as their main focus the objects and the makers, Koplos and Metcalf offer a detailed analysis of seminal works and discussions of education, institutional support, and the philosophical underpinnings of craft. Oversize, with more than 400 illustrations.